2020
DOI: 10.3389/fpls.2020.00187
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Foxtail Millet (Setaria italica L.) to Abiotic Stresses: A Special Perspective of Responses to Nitrogen and Phosphate Limitations

Abstract: Amongst various environmental constraints, abiotic stresses are increasing the risk of food insecurity worldwide by limiting crop production and disturbing the geographical distribution of food crops. Millets are known to possess unique features of resilience to adverse environments, especially infertile soil conditions, although the underlying mechanisms are yet to be determined. The small diploid genome, short stature, excellent seed production, C 4 photosynthesis, and short life cycle of foxtail millet make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 153 publications
1
23
0
Order By: Relevance
“…This is at least partially due to a high root length density at deeper soil layers (Wendling et al., 2016), which allows it to explore more soil resources and be productive during times of limited precipitation. Foxtail millet and millet species in general are considered drought tolerant (Baltensperger, 1996; Nadeem et al., 2020; Nematpour et al., 2019) due to their highly efficient C4 photosynthetic pathway (Matsuura & An, 2020). Therefore, it is possible that the two grass cover crops used in this study perform better under limited water conditions, thereby producing with more consistency, which appears to be the case for the West site.…”
Section: Discussionmentioning
confidence: 99%
“…This is at least partially due to a high root length density at deeper soil layers (Wendling et al., 2016), which allows it to explore more soil resources and be productive during times of limited precipitation. Foxtail millet and millet species in general are considered drought tolerant (Baltensperger, 1996; Nadeem et al., 2020; Nematpour et al., 2019) due to their highly efficient C4 photosynthetic pathway (Matsuura & An, 2020). Therefore, it is possible that the two grass cover crops used in this study perform better under limited water conditions, thereby producing with more consistency, which appears to be the case for the West site.…”
Section: Discussionmentioning
confidence: 99%
“…Plant roots employ adaptive mechanisms in response to environmental stimuli or nutrient variations. For instance, mild nitrogen or phosphate deficiency tends to enhance root growth for a greater nutrient absorption or translocation system ( Ahmad et al, 2018 ; Meier et al, 2020 ; Nadeem et al, 2020 ). However, how roots respond to the Mg deficiency stress is inconsistent: root growth is clearly reduced by Mg deficiency in bean plants ( Vicia faba L.) ( Neuhaus et al, 2014 ), Arabidopsis thaliana ( Gruber et al, 2013 ; Li D. et al, 2020 ), and potato ( Solanum tuberosum L.) ( Koch et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resistant starch content is another important trait specific to millet grain that awaits scientific intervention to unravel its genetics and genomics [ 45 ]. Other prospective areas of research in millets as compared to major cereals include C 4 photosynthetic traits [ 46 , 47 ] and tolerance to multiple environmental stresses [ 48 , 49 ], the development and characterization of male sterility systems [ 33 , 50 ], enhancing the shelf-life (rancidity issues) [ 51 ], reducing grain antinutrients including phytates, phenols, tannins, and enzyme inhibitors [ 52. , 53.…”
Section: Mainstreaming Millets For Ensuring Multiple Securities Durinmentioning
confidence: 99%
“…Resistant starch content is another important trait specific to millet grain that awaits scientific intervention to unravel its genetics and genomics [45]. Other prospective areas of research in millets as compared to major cereals include C 4 photosynthetic traits [46,47] and tolerance to multiple environmental stresses [48,49], the development and characterization of male sterility systems [33,50], enhancing the shelf-life (rancidity issues) [51], reducing grain antinutrients including phytates, phenols, tannins, and enzyme inhibitors [52][53][54], and addressing the issues of lodging and seed-shattering [43,55]. A recent study also reported an increased incidence of insect pests, wherein up to 150 different species were found to attack millets at different growth and developmental stages [31].…”
Section: Recent Progress In Millet Researchmentioning
confidence: 99%